The Bright Side of Fire Sales - Meier, Jean-Marie; Servaes, Henri (Review of Financial Studies, 2019)
Abstract Firms that buy assets in fire sales earn excess returns that are 2 percentage points higher than in regular acquisitions. The mechanism behind this result is the sellers’ reduced bargaining power. We find no difference in real effects or in the combined returns for buyers and sellers between fire sales and regular acquisitions, suggesting that the quality of the match is similar in both types of transactions. The externalities of fire sales for other stakeholders are limited. These results indicate that the welfare losses associated with fire sales are smaller than previously thought. Received December 17, 2015; editorial decision November 20, 2018 by Editor Itay Goldstein.